Management of Accredited Scientific Education Journals in State Islamic Universities - Albantani, Azkia Muharom; Arifin, Fatkhul (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2020)
Background of the study: The paradigm shift in the management of scientific journals from print to electronic also has an impact on accreditation policies that were initially oriented towards print scientific periodicals to the accreditation of electronic-based scientific journals.Purpose: This study aims to identify and explain the traditions and innovations in the management of accredited scientific education journals in PTKIN.Method: This research is a qualitative research with the type of field research with the orientation of empirical data collection in the field. The researcher directly reviews the documents related to management, and observes the physical / non-physical facilities used in the management of scientific journals.Findings: The results showed that of the 9 (Nine) accredited education journals of PTKIN before 2018, the most widely cited is Dinamika Ilmu Journal, amounting to 251 (two hundred fifty one) times. This has happened because Dinamika Ilmu Journal has entered the age of 18 (eighteen) years. While the Edukasia Journal is the least quoted, which is 5 (five) times. Even though the age of Edukasia Journal enters the 13th (thirteenth) year.Conclusion: From the 9 (nine) journals, only the Edukasia Journal still maintains to use the Indonesian full text even though it has been nationally accredited. While Edusains Journal, JPI Journal, Tarbiya Journal, and the Dinamika Ilmu Journal use English full text. This was done in order to support the vision of going international for his journals.